Diaquaiodido(2,3,5,6-tetra-2-pyridylpyrazine-κ(3) N (2),N (1),N (6))manganese(II) iodide monohydrate - Ha, Kwang (International Union of Crystallography, 2011)
The asymmetric unit of the title compound, [MnI(C(24)H(16)N(6))(H(2)O)(2)]I·H(2)O, consists of a cationic Mn(II) complex, an I(−) anion and a solvent water molecule. In the complex, the Mn(II) ion is six-coordinated in a considerably distorted octahedral environment defined by three N atoms of the tridentate 2,3,5,6-tetra-2-pyridylpyrazine (tppz) ligand, one I(−) anion and two O atoms of two water ligands. The dihedral angles between the pyridyl rings [maximum deviation = 0.034 (6) Å] and their carrier pyrazine ring [maximum deviation = 0.020 (6) Å] are 26.5 (2) and 27.0 (2)° for the coordinated pyridyl rings, and 51.3 (3) and 43.2 (2)° for the uncoordinated pyridyl rings. Intermolecular O—H⋯O, O—H⋯N and O—H⋯I hydrogen bonds stabilize the crystal structure.